Aplikasi Jejaring Sosial Universitas Muhammadiyah Surakarta Berbasis HTML5 dan PHP - Nugroho, Ari; , Gunawan Ariyanto, Ph.D (2014)
HTML5 or Hypertext Markup Language version to 5 is the language web programing made to replace HTML DOM Level 2, HTML4 and XHTML are used to load rich content without any additional plugins. PHP is a server-side scripting language commonly inserted into HTML pages to create dynamic websites. MySQL is a Relational Database System Implementation (RDBMS) that is commonly used to berancang database on dynamic websites. The application is made starting from requirement analysis and design followed that system design, use case diagrams and design applications. This application is built using HTML5 web programming language, server-side scripting language PHP and using MySQL database. The results of this research that is user-interface application in it contains about-face between users and applications. Applications capable of running in a web browser on a computer is the latest version. This application can help users to communicate, share information and online transactions.